Effectiveness of Different Commercial Chlorhexidine-Based Mouthwashes After Periodontal and Implant Surgery: A Systematic Review. Issue 1 (February 2019) - Chye, Rachel Mei Ling; Perrotti, Vittoria; Piattelli, Adriano; Iaculli, Flavia; Quaranta, Alessandro
Abstract : Objectives: The aim of the present study was to review the effectiveness, side effects, and patient acceptance of different concentrations and formulation of chlorhexidine-based mouthwashes used after periodontal and implant surgery. Materials and Methods: The PRISMA guideline was adopted in the search strategy using electronic databases PubMed and MEDLINE to identify randomized and case–control prospective studies on humans written in English language and published up to September 2017. Results: A total of 10 articles were selected for a total of 344 patients. Because of the significant heterogeneity of the outcome measures, meta-analysis was not performed, and the data were summarized in a table. A positive relationship between the use of chlorhexidine and reduction of plaque was found, demonstrating the effectiveness of the substance in terms of antisepsis and decrease of inflammation after periodontal and implant surgery. Conclusion: Chlorhexidine is recognized as the primary agent for plaque control and the gold standard in preventing infection, although the presence of largely known side effects would affect patient compliance. Future research should be directed at finding chlorhexidine formulation with negligible adverse effects, without compromising or even increasing its effectiveness as the antiseptics and antiplaque agent.